Effects of Thrombospondin-1 (THBS1) and Toll-like Receptor 4 (TLR-4) levels in the serum and synovial fluid of patients with knee osteoarthritis: THBS1 and TLR-4 levels in knee osteoarthritis - Xu, Yingjie; Tian, Zhen; Liang, Mingjin; Li, Xiaoyun (Journal of Medical Biochemistry, 2025)
Objective To explore the changes in and significance of Thrombospondin-1 (THBS1) and Toll-like receptor 4 (TLR-4) levels in the serum and joint fluid of patients with knee osteoarthritis (KOA).Methods 184 KOA patients who were admitted to our hospital between May 2022 and February 2025 were chosen to serve as the observation group, and another 64 healthy adults who underwent physical examinations at the same hospital during the same period composed the control group. Tumor necrosis factor-α (TNF-α), interleukin (IL)-1β, THBS1, and TLR-4 levels in the two groups' serum and joint fluid were compared. The correlations between the levels of TNF-α, IL-1β, THBS1 and TLR-4 in the serum and synovial fluid of the two groups and the severity of KOA were evaluated, and the clinical value of THBS1 and TLR-4 in the diagnosis of KOA was analyzed.Results TNF-α, IL-1β, THBS1, and TLR-4 levels in the observation group's serum and joint fluid were considerably higher than those in the control group (P
Keywords: Knee osteoarthritis; Thrombospondin-1; Toll-like receptor 4; Diagnostic value; Correlation analysis